1. Prezydent i egzekutywa we współczesnym Kirgistanie .......... 25 (Kirgistan – oblicza transformacji, 2020)
PRESIDENT AND THE EXECUTIVE IN CONTEMPORARY KYRGYZSTANIn the following chapter, the author undertakes to describe the position of the executive after the constitutional changes of 2010. The author presents the profiles of charismatic figures holding the office of president and prime minister, as well as relations between them, and shows the different approach of political leaders to the changes introduced by the Kyrgyz constitution in 2010. Despite the changes that have taken place as a result of the Tulip Revolution and the events of 2010, Kyrgyzstan has not been able to build a fully democratic legal order in which executive power will be spread between the prime minister and the president. In his text, the author tries to show that, despite the president’s institutional weakness, he still plays the most important role on the political scene of the Republic of Kyrgyzstan.